Navigating stigma, survival, and sex in contexts of social inequity among young transgender women and sexually diverse men in Kingston, Jamaica. Issue 54 (8th November 2018) - Logie, Carmen H.; Abramovich, Alex; Schott, Nicole; Levermore, Kandasi; Jones, Nicolette
Abstract: Social inequities, including stigma, criminalisation of same-sex practices, and poverty, elevate HIV exposure among young transgender women and sexually diverse men in Jamaica. Yet the ways transgender women and sexually diverse men in Jamaica navigate sex and HIV in contexts of social inequity are underexplored. The study objective was to explore experiences and perceptions of sexual decision-making and HIV risk among young (aged 18–30) sexually diverse men and transgender women in Kingston, Jamaica. We conducted a community-based qualitative study in Kingston that involved in-depth individual interviews (transgender women: n  = 20; sexually diverse men: n  = 20), 2 focus groups (transgender women: n  = 8; sexually diverse men: n  = 10) and 13 key informant interviews. Focus groups and interviews were digitally recorded, transcribed verbatim, and analysed with a thematic approach. Findings suggest that transgender women and sexually diverse men in Kingston are aware of, and managing survival challenges and HIV risks in contexts of social inequity. Daily survival challenges include stigma and a lack of human rights protections that contributed to barriers to employment, housing, healthcare, education, and exposure to violence. Challenges maintaining sexual relationships included the need to hide for safety, often resulting in difficulties forming lasting relationships. These survival and relationship challenges converged to lower self-esteem and self-acceptance. In the face of these challenges, participants navigated sexual risk and pleasure. Findings provide insight into agency and sexual decision-making processes in contexts of social inequities. Findings can inform multi-level strategies to promote social equity, sexual health, and HIV prevention with young transgender women and sexually diverse men in Jamaica.